Dobra śmierć – czyli jaka? Próba odpowiedzi na pytanie na podstawie nauczania K. Rahnera, H. U. von Balthasara i J. Ratzingera (Benedykta XVI) - Kulik, Bogdan (Poznańskie Studia Teologiczne, 2017)
On July 22, 1908, Pope Pius X established the Association of Our Lady of a Happy Death as universal for the whole Church. On May 1987, the Primate of Poland, Cardinal Joseph Glemp, approved the Polish Branch of the Association at the Shrine to the Virgin Mary in Górka Klasztorna. He also permitted the Missionaries of the Holy Family to carry out this work. The purpose of the Association is the propagation of prayer and preparation for a good death. The question is, however, can death be good? If so, what is a good death? The article titled „What makes a good death? An attempt to answer the question based on the teachings of K. Rahner, H.U. von Balthasar and J. Ratzinger – Benedict XVI“ is an analysis of the thoughts of the three great contemporary theologians. It does not, however, aim to analyze deeply the mutual similarities and differences between the German-speaking theologians. The study aims at explaining what we really ask God for when praying for a „happy death”. Even a cursory reading of selected books by Rahner, von Balthasar and Ratzinger – Benedict XVI reveals that thinking about death as something good is not unreasonable. Why? Because the positive aspect of dying does not come from the nature of death, but from God’s action in it. It was Him who in the Person of Jesus Christ became man and conquered the hell of death (Ratzinger) by transforming a “bad death” into a “good one” (von Balthasar), and thus gained eternal redemption for us (Rahner).